Syirik di era modern: bentuk tantangan dan solusi mengatasinya - 'Aina', Sadatul; Fudhla, Mahmudatun; Anwar, Silvia Fitria; Muttaqin, Muhammad Imamul (Maliki Interdisciplinary Journal, 2025)
This study discusses the phenomenon of modern shirk that occurs in society due to factors of technological development and progress in the modern era, such as belief in zodiac predictions, the use of prediction services through digital applications or SMS, and the influence of misleading horror films. This phenomenon shows that although shirk is considered an old problem, its form still exists and develops in a more disguised form in everyday life. This study aims to provide an understanding of the form of challenges of modern shirk and the solutions that can be done to overcome it and provide an understanding of the importance of maintaining the purity of monotheism amidst the influence of technology that can be misleading. The method used in this study is library research, namely by collecting data from relevant literature sources from the Qur'an, Hadith, books, and scientific articles. Therefore, by understanding modern shirk, it is hoped that this study can be a guide for Muslims to increase awareness, strengthen faith, increase worship and avoid all forms of associating partners with Allah in everyday life.